A Handbook of Case Studies in Finance - Sikarwar, Tarika (Cambridge Scholars Publishing, 2017)
This book links the theory of finance to the decisions related to various aspects of the financial management of an organisation. In order to provide the reader with a better understanding of the concept of finance, a theoretical guide to related terminology is included here. The case studies brought together require students to look deep into the concepts of finance in order to solve the problems and issues they present. The case studies here focus on important concepts of finance which help students to relate the concept with decision-making processes.